CUSTOMER SATISFACTION OF PEOPLE IN THE SHOPPING OF BRANDED AND NON-BRANDED ARTICLES THROUGH ONLINE-OFFLINE MODE - Pal, Rohit Kumar; Chaudhary, Uditanshu (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This study attempts to compare the customer satisfaction of people in the shopping of branded and non-branded articles through online-offline mode. The null hypotheses were formulated for this study. The researcher has used a cross-sectional research design. The researcher has employed a quantitative survey method in the present study. Sample of the present study involved 600 customers above 18 years who are residing in the six blocks of district Dehradun. Purposive sampling technique was used to select the sample for the study. Consequently, 290 male and 310 female customers from the Dehradun district were chosen. Customer satisfaction was the dependent variable and type of articles and mode of shopping were the independent variables involved in the present study. Customer Satisfaction Scale developed by the researcher has been used to collect the data. Mean, S.D. and ‘t’ test have been used for the statistical analysis. Findings revealed that there was a significant difference in the customer satisfaction of people in the shopping of branded and non-branded articles. Customer satisfaction of people in the shopping of non-branded articles was found higher as compared to the shopping of branded articles. There was found a significant difference in the customer satisfaction of people in the shopping through online-offline mode. Customer satisfaction of people in the shopping through offline mode has been found higher as compared to the shopping through online mode.